Neutrino Physics : Its Impact on Particle Physics, Astrophysics and Cosmology - Proceedings of the Carolina Symposium on Neutrino Physics. - Bahcall, J. (World Scientific Publishing Company, 2001)
Neutrinos play a key role in many areas of particle physics, nuclear physics and astrophysics. The recent discovery of neutrino oscillation has given the first hint of new physics beyond the standard model. Clearly, it is extremely important to study further the oscillation and other fundamental properties of neutrinos. It is also important to improve our knowledge of neutrino-nucleus reactions, which are crucial for understanding a large class of astrophysical phenomena. These and many other interesting questions can be investigated at stopped pion neutrino facilities like the one planned for.